REMEDIASI PEMBELAJARAN MELALUI FAST FEEDBACK BERBANTUAN POWERPOINT UNTUK MEREDUKSI MISKONSEPSI MATERI CAHAYA - Herlinda, Herlinda; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was conducted to determine the effectiveness of fast feedback method assisted by powerpoint to reduce students misconception on light material in SMA Islam Bawari Pontianak.  This study was quasi  pre-experimental design with one group pre-test post-test design. Data collection tool form multiple choice questions with closed reasons and three alternative answers. The sample was 31 students of class XI IPA selected intact group. The average decrease of student misconceptions were 34,41% with significant conceptual change by Mc Nemar test ( ). There was significant conceptual change after remediation by apply fastfeddback method assisted by powerpoint to reduce students misconception on light material. Result reveal that the effectiveness level was 0,56 (medium). This research is expected to be used as an alternative remediation activities to reduce misconception in learning process on light material.Keywords:   Remediasi, Fast Feedback, Miskonsepsi.